THE INFLUENCE OF OWNER EDUCATION LEVELS, OWNER ACCOUNTING KNOWLEDGE, BUSINESS SCALE, AND BUSINESS AGE ON THE USE OF ACCOUNTING INFORMATION IN MSME’S IN WONOGIRI - Icuk Rangga Bawono (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
This research aims to determine The Influence of Owner Education Levels, Owner Accounting Knowledge, Business Scale, and Business Age on the Use of Accounting Information in MSMEs in Wonogiri Sub-district. The method of data collection conducted in this study is a survey method with a questionnaire. This research was conducted at Regional Wonogiri regency. The dependent variable of this study is owner education levels, owner accounting knowledge, business scale, and business age. The sample in this study amounted to 45 samples and Research is quantitative which uses an analytical approach descriptive. The level of education has a significant influence on the use of accounting information, accounting knowledge has a significant influence on the use of accounting information, business scale does not have a significant influence on the use of accounting information, business age has a significant influence on the use of accounting information, accounting knowledge has the most influence dominant to the use of accounting information in Micro, Small and Medium Enterprises (MSMEs) in Wonogiri District.